2018
DOI: 10.1016/j.ccr.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Current advances on ruthenium(II) N-heterocyclic carbenes in hydrogenation reactions

Abstract: This review provides a brief overview of advances on ruthenium(II) N-heterocyclic carbene complexes 30 (NHCs) applied for hydrogenation reactions undertaken during the last five years. Several structural 31 motifs, containing mono-, bi-, tri-and tetradentate binding modes of the NHCs are discussed in combi-32 nation with a variety of different wingtip substituents to provide active catalysts for hydrogenation reac-33 tions. While bidentate ligands are the more active catalysts than their monodentate analogues,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 130 publications
(61 reference statements)
0
56
1
Order By: Relevance
“…Subsequent optimization revealed the following facts and trends: (i) NHC's with an unsaturated backbone gave better results than their saturated cousins; (ii) the nature of the N‐substituent is also important even though its exact role remains to be elucidated: for the time being, [(IPr)(η 6 ‐cymene)RuCl 2 ] ( 3 c ) works best, followed by [(IMes)(η 6 ‐cymene)RuCl 2 ] ( 3 b ); the use of related NHC's ( 4 d – g ) as ancillary ligands resulted in failure; (iii) likewise, replacement of the NHC by R 3 P (R=Cy, Ph) brings hydrogenative metathesis to a hold; (iv) constant irradiation of the reaction mixture with a UV lamp is necessary; attempts to drive the reaction by thermal de‐coordination of the p ‐cymene ligand led to mixtures that contain only minute amounts of the desired product; (v) while the [Cp*Ru] catalysts previously used operate best in chlorinated media, the switch from 1,2‐dichloroethane to toluene resulted in a significant increase in yield; (vi) just like in our previous study on gem ‐hydrogenation, the substitution of the alkene strongly impacts on the outcome; enyne 1 b (R=Me) bearing a methyl cap on the olefinic site proved to be optimal. When the reaction of this substrate is carried out with 3 c (10 mol %) in toluene under H 2 atmosphere (balloon) and irradiation with a UV lamp ( λ =370±40 nm), the metathesis reaction is remarkably clean and essentially quantitative (see the SI), affording analytically pure 2 in 95 % yield after flash chromatography.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent optimization revealed the following facts and trends: (i) NHC's with an unsaturated backbone gave better results than their saturated cousins; (ii) the nature of the N‐substituent is also important even though its exact role remains to be elucidated: for the time being, [(IPr)(η 6 ‐cymene)RuCl 2 ] ( 3 c ) works best, followed by [(IMes)(η 6 ‐cymene)RuCl 2 ] ( 3 b ); the use of related NHC's ( 4 d – g ) as ancillary ligands resulted in failure; (iii) likewise, replacement of the NHC by R 3 P (R=Cy, Ph) brings hydrogenative metathesis to a hold; (iv) constant irradiation of the reaction mixture with a UV lamp is necessary; attempts to drive the reaction by thermal de‐coordination of the p ‐cymene ligand led to mixtures that contain only minute amounts of the desired product; (v) while the [Cp*Ru] catalysts previously used operate best in chlorinated media, the switch from 1,2‐dichloroethane to toluene resulted in a significant increase in yield; (vi) just like in our previous study on gem ‐hydrogenation, the substitution of the alkene strongly impacts on the outcome; enyne 1 b (R=Me) bearing a methyl cap on the olefinic site proved to be optimal. When the reaction of this substrate is carried out with 3 c (10 mol %) in toluene under H 2 atmosphere (balloon) and irradiation with a UV lamp ( λ =370±40 nm), the metathesis reaction is remarkably clean and essentially quantitative (see the SI), affording analytically pure 2 in 95 % yield after flash chromatography.…”
Section: Methodsmentioning
confidence: 99%
“…In light of N‐heterocyclic carbene‐metal (NHC‐M) complexes can act as robust and viable catalysts in a broad range of reactions, various strategies have been developed for their immobilization . Among them, self‐supporting strategy may represent one of the most practical and efficient approaches .…”
Section: Fabrication Of Pomp‐nhc‐m By Direct Knitting With Different mentioning
confidence: 99%
“…Half-sandwich complexes of group 8 metals with a characteristic piano-stool architecture are privileged structures in organometallic and catalysis research, 15 and have found wide application in bioinorganic and medicinal chemistry. 3,69 In this context, 1-methyl-4-(propan-2-yl)benzene ( para -cymene, p -cym) plays a predominant role because it represents an easily accessible formally neutral η 6 -coordinating arene ligand and its ruthenium(II) complex [{Ru( p -cym)Cl 2 } 2 ] is commercially available.…”
Section: Introductionmentioning
confidence: 99%